KEKUATAN ALAT BUKTI PETUNJUK DALAM PERKARA TINDAK PIDANA KORUPSI (TINJAUAN PASAL 26 A UNDANG-UNDANG NOMOR 31 TAHUN 1999 Jo. UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KO - Denny Sillalahi (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT It is recognized by the public that corruption is a major problem of this nation that should be addressed as effectively as possible, because otherwise this nation would be worse off into destruction, corruption proven to cause widespread poverty, rising unemployment, growing state debt, the worse public services, the construction of the hampered, rampant abuse of authority, theft of public money on a large scale, weak rule of law and the existence of legal handling of selective logging. Keep in mind for the general public in dealing bahwasannya in corruption cases required at least two valid evidence to be able to penalize a person who lodged the case, therefore, is not an easy thing for a judge to penalize the perpetrators of the corruption cases.The method I use is the method of Normative Legal research is conducted to obtain primary legal materials, legal materials and secondary materials tertiary law regarding criminal law review, the instructions related to the strength of the evidence as valid evidence in corruption cases and the use of evidence of instructions as the basis for court decisions and the type of research used in this study is the approach of the Act (the statute approach) whose formulation with respect to the norm ambiguity on the formulation of Article 26 a of Law No. 31 of 1999 Jo Act No. 20 of 2001 on the Amendment Law Number 31 Year 1999 on Eradication of Corruption. The nature of this research is descriptive analysis, which is explained in full, clear and detailed and systematic research on the strength of evidence in the instructions as valid evidence in corruption and the use of evidence as a basis for court rulings instructions.Based on the results of the study authors conclude that the attitude of the judge in determining the evidence instructions, contained in Article 188 paragraph (3) Criminal Procedure Code requires the judge to do it again wise wise, because the evidence in this manual entirely in the hands of the judge then it is proper assessment of the strength of evidence must be made by the judge with the wise, thoughtful, and objective.Combating corruption can not be done by the Commission and law enforcement alone, but also requires a synergy and a common perception of all components of the nation. Hope author community participation is needed and has significance in combating corruption strategy. On activities that are repressive, the public could be the reporting of alleged corruption and bureaucracy, especially in the public service, while in terms of preventive, primary act of eradication of corruption can be started from the respective self-awareness to obey the law and stay away from corrupt actions.